Response Letter to the Editor in Reference to Letter to the Editor about "Does Overall Catastrophic Health Care Expenditure Make Sense"? - Manal ETEMADI; Aidin ARYANKHESAL (Tehran University of Medical Sciences, 2018)
Response Letter to the Editor in Reference to Letter to the Editor about "Does Overall Catastrophic Health Care Expenditure Make Sense"?